When dogs react: The role of caregiver factors and fear/anxiety in reactive and aggressive manifestations - Lavrador, Catarina; Graça-Pereira, Gonçalo; Batista, Maria T (Elsevier, 2025)
Reactive/aggressive manifestations (R/AMs) are a problematic behavior that significantly affects the well-being of both dogs and their caregivers, reducing their quality of life and undermining the stability of the human–animal bond. This cross-sectional study (N = 730) focused primarily on caregiver-related characteristics associated with R/AMs in dogs, followed by an analysis of the contribution of fear/anxiety. Data were collected through an online questionnaire. Starting from a broad set of variables related to the dog (e.g., age), caregiver sociodemographic characteristics (e.g., gender), intrapersonal variables (e.g., mental health), interpersonal variables (e.g., attitudes), and caregiving and management practices (e.g., professional training), Pearson correlations were calculated between all variables and this problematic behavior. All variables that were significantly correlated with R/AMs were included in multiple linear regression models to identify the most relevant predictors from this broad set of factors. The results highlight the role of caregiver-dog interpersonal dynamics and the relevance of fear/anxiety in the R/AMs. Younger dogs, those cared for by male caregivers, dogs whose caregivers reported higher perceived caregiving costs and higher caregivers stress levels, more positive attitudes toward aversive training methods, and a lower ability to recognize chronic pain, were described as showing higher levels of R/AMs Together, these variables explained 15.8 % of the variance in R/AMs. When fear/anxiety was added to the model, the amount of explained variance increased substantially, with the final model accounting for 41 % of the variability in this problematic behavior. These findings emphasize the importance of the caregiver-dog relationship in understanding R/AMs and suggest that fear/anxiety is a core underlying component of this problematic behavior. Behavioral interventions for R/AMs should address not only the dog’s behavior and emotional state, but also caregiver-related factors. Consideration should be given to the use of strategies that improve caregiver’s knowledge of indicators of pain and discomfort in dogs, encourage the use of reward-based training, and support reduced caregiving costs.
Keywords: Aversive training attitudes; Caregiver related factors; Chronic pain recognition; Fear and anxiety; Human-dog relationship; Reactive/ aggressive manifestations